Clinical characteristics and outcomes of liver abscesses: a 12-year retrospective analysis from a tertiary care center in the United Arab Emirates - Agha, Adnan; Farooqi, Mohammed Fareeduddin; Khan, Maria; Nabi, Noria Ghulam; Siddiqua, Amatur Rehman (Frontiers in Medicine, 2025)
BackgroundLiver abscesses are a cause of morbidity worldwide and their outcomes can vary remarkably in various regions of the world. In the United Arab Emirates (UAE) the clinical picture of liver abscesses is not fully understood. We aimed to fill this gap by analyzing the clinical features, microbiology, and outcomes for patients with liver abscess over a 12-year period.MethodsWe conducted a retrospective observational study of all adult patients (≥18 years) with confirmed diagnosis of liver abscess at Tawam Hospital, Al Ain, UAE, from January 2012 to January 2024. Electronic medical records were reviewed to extract demographic, clinical, laboratory, radiological, and microbiological data. Patients were then classified as either having pyogenic liver abscess (PLA) or amoebic liver abscess (ALA). Statistical analyses were performed to identify predictors of morbidity and mortality.ResultsOf 158 patients screened, 79 had confirmed liver abscesses (71 pyogenic, 8 amoebic). The mean age was 56.8 ± 16.2 years, with male predominance (65.8%). The commonest clinical findings were abdominal pain (73.4%), fever (68.4%), and nausea/vomiting (45.6%). Diabetes mellitus was found in 35.4% of patients, while malignancy was identified in 30.4%. Klebsiella pneumoniae was the most frequently isolated organism (40.0% of positive pus cultures), followed by Escherichia coli (14.0%). However, E. coli, particularly ESBL-producing strains, showed disproportionately high mortality (80.0%) compared to K. pneumoniae (2.6% mortality). The overall mortality rate was 15.2% (12/79), with 83.3% (10/12) directly attributable to liver abscess complications. ICU admission was required in 20.3% of cases. In univariate analysis, predictors of mortality included age >65 years (OR 12.2, 95% CI 2.9–51.2, p < 0.001), serum albumin <30 g/L (OR 17.6, 95% CI 2.2–142.8, p < 0.001), and presence of multiple abscesses (OR 4.5, 95% CI 1.3–15.6, p = 0.02).ConclusionThe overwhelming majority of patients with liver abscesses at high-risk for complications respond favorably to antimicrobial therapy. However, the most striking finding was the unexpectedly observed mortality associated with E. coli, especially ESBL strains (80% mortality), something that underscores the need for rapid diagnosis and robust empiric coverage for resistant organisms in the severely ill. Our findings identify increased frequency of underlying malignancy which emerged as a major determinant of mortality, reinforcing the need for comprehensive cancer screening into the diagnostic workup of patients presenting with liver abscess.